Analisis Kelayakan Finansial Usaha Sayuran Hidroponik di CV Pagi Berkah Mandiri Bogor - Manurung, Putri Beata; Santoso, Siswanto Imam; Ekowati, Titik (Universitas Galuh, 2025)
Hydroponic vegetable business is an alternative farming in urban areas. The emergence of many businesses creates market competition that affects business finances, especially small hydroponic vegetable businesses. This study aims to analyze the income of the hydroponic business at CV Pagi Berkah Mandiri and determine the feasibility of the investment invested in the company. The research method used is the case study method. The analysis method on the financial aspect is analyzed using the income analysis method, investment criteria analysis consisting of Net Present Value (NPV), Profitability Index (PI), Payback Period (PP), Return on Investment (ROI), Internal Rate of Return (IRR), Gross B / C Ratio and sensitivity analysis. The results of the analysis of 3 years of business data show that the average income obtained in 1 year is IDR 268,558,769. The results of the financial analysis with investment criteria show an NPV value of IDR 154,881,734, a PI value of 1.24, an ROI of 124.29%, PP for 2.12 years and a B / C Ratio of 1.75. The results indicate that the business is feasible to be implemented and developed. The results of the sensitivity analysis of the decrease in revenue and the increase in costs of 3.33% still represent that the business is feasible to be implemented.